An analysis of multiparty bargaining models for global supply chains - Blasi, Jeremy; Bair, Jennifer (Geneva, 2018)
"This working paper proceeds as follows. After briefly reviewing our methodology, we provide an overview of the multiparty bargaining models reviewed in our study. Next, we review the key regulations incorporated into these models concerning lead firm procurement and/or sourcing practices, illustrating these principles with capsule summaries of notable cases. We then review mechanisms for enforcing lead firm commitments, including mediation, arbitration, enforcement in court, and transparency. Finally, we conclude with general observations concerning factors favouring the development of the instruments and arrangements reviewed. We hope that the strategies and policies outlined in this report can serve as useful references for worker organizations, industry, and government as they develop the next generation of initiatives to realize decent work in supply chains."